Results 1 to 2 of 2

Math Help - Problem

  1. #1
    Member
    Joined
    Feb 2009
    From
    Chennai
    Posts
    148

    Problem

    Hi

    Define

     \[ g(x) =  \left\{<br />
                 \begin{array}{lll}<br />
                  x+2 & if & \ -3 \leq x \leq -1 \\<br />
                  -x &  if  & -1 < x \leq 1, \\<br />
                  x-2 & if & 1<x \leq 3.<br />
                  \end{array}<br />
                   \right.<br />
                    \]


    Now let  f(x)=g(x-6n)+ 2n for 6n-3 \leq  x \leq 6n+3 , \ n \in \mathbb{Z}.Prove that f takes each of it values three times
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor Drexel28's Avatar
    Joined
    Nov 2009
    From
    Berkeley, California
    Posts
    4,563
    Thanks
    21
    Quote Originally Posted by Chandru1 View Post
    Hi

    Define

      g(x) =  \left\{<br />
                 \begin{array}{lll}<br />
                  x+2 & if & \ -3 \leq x \leq -1 \\<br />
                  -x &  if  & -1 < x \leq 1, \\<br />
                  x-2 & if & 1<x \leq 3.<br />
                  \end{array}<br />
                   \right.<br />


    Now let  f(x)=g(x-6n)+ 2n for 6n-3 \leq  x \leq 6n+3 , \ n \in \mathbb{Z}.Prove that f takes each of it values three times
    I'm tired and going to bed, but I fixed your latex.
    Follow Math Help Forum on Facebook and Google+

Search Tags


/mathhelpforum @mathhelpforum